Collaborative Governance In Post-Covid-19 Economic Recovery: A Case Study Of The "Mustika Desa" Program In Temanggung Regency - Aksan, Aksan (Journal Of Social Science (JoSS), 2025)
This study explores the collaborative process in the Mustika Desa program in Temanggung Regency. The collaboration phenomenon in this program involves various cross-sector actors who are interested in recovering the economy after the Covid-19 pandemic. This study is interesting because addressing complex public issues is often ineffective if actors work in isolation, while collaboration opens up space for the unification of resources, knowledge, and interests to achieve a common goal. Therefore, this study focuses on the process of collaboration stages in the Mustika Desa program. The study uses a qualitative approach with a case study method, combining theoretical frameworks with empirical findings in the field. The analysis unit is focused on Temanggung Regency, with primary data obtained through in-depth interviews with key informants, as well as secondary data from previous studies and official documents of related institutions. This study found that the collaboration process in the Mustika Desa program takes place through four main stages: formal and informal face-to-face dialogue to unite views; building trust and commitment that triggers participation; the formation of mutual understanding through the agreement of rules and concrete support; and the achievement of temporary results in the form of positive dynamics in three priority programs—Yard Farmers, Land Conservation, and Waste-Free Villages—which are adjusted to the aspirations of the community and local conditions. As a form of actors' choice of strategy, collaboration is a mechanism to bridge obstacles and take advantage of opportunities from formal policies, while ensuring that programs remain relevant to the needs